Influenza Season Hospitalization Trends in Israel: A Multi‐Year Comparative Analysis 2005/2006 Through 2012/2013. Issue 9 (1st September 2017) - Glatman‐Freedman, Aharona; Kaufman, Zalman; Stein, Yaniv; Sefty, Hanna; Zadka, Hila; Gordon, Barak; Meron, Jill; Gordon, Ethel‐Sherry; Dichtiar, Rita; Haklai, Ziona; Afek, Arnon; Shohat, Tamy
Abstract : BACKGROUND: Influenza‐related morbidity impacts healthcare systems, including hospitals. OBJECTIVE: To obtain a quantitative assessment of hospitalization burden in pediatric and internal medicine departments during influenza seasons compared with the summer months in Israel. METHODS: Data on pediatric and internal medicine hospitalized patients in general hospitals in Israel during the influenza seasons between 2005 and 2013 were analyzed for rate of hospitalizations, rate of hospitalization days, hospital length of stay (LOS), and bed occupancy and compared with the summer months. Data were analyzed for hospitalizations for all diagnoses, diagnoses of respiratory or cardiovascular disease (ICD9 390‐519), and influenza or pneumonia (ICD9 480‐487), with data stratified by age. The 2009‐2010 pandemic influenza season was excluded. RESULTS: Rates of monthly hospitalizations and hospitalization days for all diagnoses were 4.8% and 8% higher, respectively, during influenza seasons as compared with the summers. The mean LOS per hospitalization for all diagnoses demonstrated a small increase during influenza seasons as compared with summer seasons. The excess hospitalizations and hospitalization days were especially noticed for the age groups under 1 year, 1‐4 years, and 85 years and older. The differences were severalfold higher for patients with a diagnosis of respiratory or cardiovascular disease and influenza or pneumonia. Bed occupancy was higher during influenza seasons compared with the summer, particularly in pediatric departments. CONCLUSIONS: Hospital burden in pediatric and internal medicine departments during influenza seasons in Israel was associated with age and diagnosis. These results are important for optimal preparedness for influenza seasons.